Enabling insights and analytics with data streaming architectures and pipelines using Kafka and Hadoop (O'Reilly Media, 2019)
"In a large global health services company, streaming data for processing and sharing comes with its own challenges. Data science and analytics platforms need data fast, from relevant sources, to act on this data quickly and share the insights with consumers with the same speed and urgency. Join Mohammad Quraishi (Cigna) to learn why streaming data architectures are a necessity--Kafka and Hadoop are key. Mohammad outlines architectures centered around the Hadoop Platform and Kafka that were implemented to support a variety of integration and analytics requirements. This session was recorded at the 2019 O'Reilly Strata Data Conference in San Francisco."--Resource description page